Associations between double-checking and medication administration errors: a direct observational study of paediatric inpatients. Issue 4 (7th August 2020) - Westbrook, Johanna I; Li, Ling; Raban, Magdalena Z; Woods, Amanda; Koyama, Alain K; Baysari, Melissa Therese; Day, Richard O; McCullagh, Cheryl; Prgomet, Mirela; Mumford, Virginia; Dalla-Pozza, Luciano; Gazarian, Madlen; et al.
Abstract : Background: Double-checking the administration of medications has been standard practice in paediatric hospitals around the world for decades. While the practice is widespread, evidence of its effectiveness in reducing errors or harm is scarce. Objectives: To measure the association between double-checking, and the occurrence and potential severity of medication administration errors (MAEs); check duration; and factors associated with double-checking adherence. Methods: Direct observational study of 298 nurses, administering 5140 medication doses to 1523 patients, across nine wards, in a paediatric hospital. Independent observers recorded details of administrations and double-checking (independent; primed—one nurse shares information which may influence the checking nurse; incomplete; or none) in real time during weekdays and weekends between 07:00 and 22:00. Observational medication data were compared with patients' medical records by a reviewer (blinded to checking-status), to identify MAEs. MAEs were rated for potential severity. Observations included administrations where double-checking was mandated, or optional. Multivariable regression examined the association between double-checking, MAEs and potential severity; and factors associated with policy adherence. Results: For 3563 administrations double-checking was mandated. Of these, 36 (1·0%) received independent double-checks, 3296 (92·5%) primed and 231 (6·5%) no/incomplete double-checks. For 1577 administrations double-checking was not mandatory, but in 26·3% (n=416) nurses chose to double-check. Where double-checking was mandated there was no significant association between double-checking and MAEs (OR 0·89 (0·65–1·21); p=0·44), or potential MAE severity (OR 0·86 (0·65–1·15); p=0·31). Where double-checking was not mandated, but performed, MAEs were less likely to occur (OR 0·71 (0·54–0·95); p=0·02) and had lower potential severity (OR 0·75 (0·57–0·99); p=0·04). Each double-check took an average of 6·4 min (107 hours/1000 administrations). Conclusions: Compliance with mandated double-checking was very high, but rarely independent. Primed double-checking was highly prevalent but compared with single-checking conferred no benefit in terms of reduced errors or severity. Our findings raise questions about if, when and how double-checking policies deliver safety benefits and warrant the considerable resource investments required in modern clinical settings.